Avulsion fracture of the trochanter minor in the adolescent - Memminger, Michael Kurt (Acta Biomedica Atenei Parmensis, 2018)
In the adolescent, the trochanter minor fracture occurs in pathological traction of the iliopsoas tendon, the minor fragment dislocates cranially. The therapy is conservative, the fragment remains dislocated cranially, where it heals with the femur. A limited hip function in terms of impingement symptoms is not known. We present the case of a 14-year-old boy: the lesion occurred during sports activities (running) through hyperextension and rotation trauma. The treatment was conservative, functional limitations did not remain.